2019
DOI: 10.1038/s41467-019-10554-w
|View full text |Cite
|
Sign up to set email alerts
|

The prion-like domain of Drosophila Imp promotes axonal transport of RNP granules in vivo

Abstract: Prion-like domains (PLDs), defined by their low sequence complexity and intrinsic disorder, are present in hundreds of human proteins. Although gain-of-function mutations in the PLDs of neuronal RNA-binding proteins have been linked to neurodegenerative disease progression, the physiological role of PLDs and their range of molecular functions are still largely unknown. Here, we show that the PLD of Drosophila Imp, a conserved component of neuronal ribonucleoprotein (RNP) granules, is ess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3
1

Relationship

3
6

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 68 publications
(107 reference statements)
3
26
0
Order By: Relevance
“…This suggests that oskar granules in Hrp48-depleted/truncated lines have altered physical properties that impair their native function, and imply a role of the Hrp48-PrLD in modulating granule material properties. Similar observation has been made in case of Imp, a conserved component of Drosophila neuronal RNP granules (Vijayakumar et al, 2019). Biomolecular condensates exhibit a continuum of material and emergent properties that can be harnessed by the cell to specific needs (Alberti, 2017).…”
Section: Resultssupporting
confidence: 86%
“…This suggests that oskar granules in Hrp48-depleted/truncated lines have altered physical properties that impair their native function, and imply a role of the Hrp48-PrLD in modulating granule material properties. Similar observation has been made in case of Imp, a conserved component of Drosophila neuronal RNP granules (Vijayakumar et al, 2019). Biomolecular condensates exhibit a continuum of material and emergent properties that can be harnessed by the cell to specific needs (Alberti, 2017).…”
Section: Resultssupporting
confidence: 86%
“…Further characteristic of a liquid state, neuronal granules are subject to rapid internal rearrangements, as visualized in fluorescence recovery after photobleaching (FRAP) experiments after half‐bleaching of granules. Intra‐granule diffusion of molecules is also associated with exchange of molecules with the surrounding cytoplasmic environment, typically on the time‐scales of seconds to minutes, although turnover rates appear to depend on granule type and/or component …”
Section: Neuronal Rnp Granules Are Dynamic Membrane‐less Condensatesmentioning
confidence: 99%
“…As most of the prion‐like domains studied so far trigger phase separation in vitro, the prevalent view is that they may function as autonomous modules for RNP granule assembly . More recent work has, however, suggested that they may rather have chaperone‐like functions, behaving as modifiers of phase separation and granule material properties . Although such a protein‐centric way of considering RNP assembly fits with the fact that neuronal RNP granules have historically been defined based on their characteristic protein markers (eg, FMRP, ZBP1, Staufen 2, Barentsz, CPEB, TDP‐43), it does not take into account the contribution of a major player in the system: RNA.…”
Section: How and Where Are Neuronal Rnp Granule Assembled?mentioning
confidence: 99%
“…In vitro and ex vivo live-imaging of fluorescently-tagged mRNAs or their associated RBPs has revealed that RNP assemblies are transported to distal axons through active, bi-directional motion characterized by the presence of both anterograde and retrograde processive events interspaced by long stationary phases (Knowles et al, 1996; Tiruchinapalli et al, 2003; Leung et al, 2006, 2018; Nalavadi et al, 2012; Alami et al, 2014; Medioni et al, 2014; Gopal et al, 2017; Wong et al, 2017; De Graeve and Besse, 2018; Turner-Bridger et al, 2018; Vijayakumar et al, 2019). Long-range transport of RNP granules along the axon shaft relies on the integrity of the microtubule cytoskeleton (Knowles et al, 1996; Medioni et al, 2014; Leung et al, 2018) and likely requires the combined activity of kinesin and dynein motors, although direct evidence is still scarce (Das et al, 2019).…”
Section: Membrane-bound Organelles As Vehicles For Axonal Transport Omentioning
confidence: 99%